2017
DOI: 10.1501/vetfak_0000002778
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara vitulorum ile doğal enfekte buzağılarda serum haptoglobin düzeyi, oksidatif belirteçler ve bazı biyokimyasal parametrelerin düzeyinin belirlenmesi

Abstract: Özet: Bu çalışmanın amacı Toxocara vitulorum ile doğal enfekte buzağılarda serum haptoglobin düzeyi, oksidatif belirteçler ve bazı biyokimyasal parametrelerin düzeylerinin belirlenmesi ve diyagnostik önemlerinin araştırılmasıdır. Bu amaçla, kontrol grubu olarak 10 adet klinik açıdan sağlıklı buzağı ve 1-3 aylık, 20 adet farklı cinsiyette T. vitulorum ile doğal enfekte toplam 30 adet montofon ırkı buzağı kullanıldı. Biyokimyasal analizler için kan örnekleri V. jugularis'ten alındı. Alınan kan örneklerinden bir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In studies conducted on cattle, MDA levels were reported to be affected in some bacterial, viral, and parasitic diseases. It is reported that the level of MDA increases in skin papilloma (Arslan et al, 2018), Fasciola gigantica (Bahrami et al, 2014), Neosporiosis (Glombowsky et al, 2017), Coccidiosis (Yilmaz andIssi, 2014), Babesiosis (Saleh, 2009), Anaplazmosis (Esmaeilnejad et al, 2018), Dictyocaulus viviparus (Deǧer et al, 2008), Hypoderma spp (Merhan et al, 2017), Theileriosis (Kızıl et al, 2011), Toxocara vitulorum (Bozukluhan et al, 2017), Hidatidosis (Heidarpour et al, 2013), Tuberculosis (Kızıl and Keltek, 2017), listeriosis (Jaguezeski et al, 2018), FMD (Khoshvaghti et al, 2014;Uzlu et al, 2016), Omphalitis (Bozukluhan et al, 2016), Brucellosis (Perin et al, 2017), Mastitis (Deveci and Güven, 2008), anthrax vaccine administration (Doğan et al, 2021), Dystocia (Bayyit and Merhan, 2020), and transplanted cattle (Chirase et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted on cattle, MDA levels were reported to be affected in some bacterial, viral, and parasitic diseases. It is reported that the level of MDA increases in skin papilloma (Arslan et al, 2018), Fasciola gigantica (Bahrami et al, 2014), Neosporiosis (Glombowsky et al, 2017), Coccidiosis (Yilmaz andIssi, 2014), Babesiosis (Saleh, 2009), Anaplazmosis (Esmaeilnejad et al, 2018), Dictyocaulus viviparus (Deǧer et al, 2008), Hypoderma spp (Merhan et al, 2017), Theileriosis (Kızıl et al, 2011), Toxocara vitulorum (Bozukluhan et al, 2017), Hidatidosis (Heidarpour et al, 2013), Tuberculosis (Kızıl and Keltek, 2017), listeriosis (Jaguezeski et al, 2018), FMD (Khoshvaghti et al, 2014;Uzlu et al, 2016), Omphalitis (Bozukluhan et al, 2016), Brucellosis (Perin et al, 2017), Mastitis (Deveci and Güven, 2008), anthrax vaccine administration (Doğan et al, 2021), Dystocia (Bayyit and Merhan, 2020), and transplanted cattle (Chirase et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SAA, which can increase over 1000 times in the circulation in inflammatory conditions, has functions such as preventing antibody formation by lymphocytes, inducing collagenase, and increasing leukocyte adhesion to endothelial cells (Petersen et al, 2004;Murata et al, 2004). The levels of SAA increases in bacterial (Merhan et al, 2017b), viral (Merhan et al, 2017c), and parasitic infections (Bozukluhan et al, 2017). In addition, serum levels increase in ketosis (Brodzki et al, 2021), after operations (Bozukluhan and Gökçe, 2007), and in fasting for more than 3 days (Katoh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%